Robot posture generation method for laser melting deposition. Issue 6 (6th August 2020) - Zheng, Huadong; Wang, Caidong; Fei, Zhigen; Chen, Lumin; Cheng, Yan
Abstract : Purpose: This paper aims to provide a posture generation method of robot deposition paths based on intersection topology, which is helpful to contribute to improving the flexibility and deposition capability of the deposition system. Design/methodology/approach: Via the geometry information and normal vector information of the stereolithography (STL) model, the intersecting edge information is generated and the topological relationship of the model is established. Through the removal of redundant points for the STL model and the sort of robot path points, the position information of robot path points is obtained. According to the geometric relationship between the normal vector information of the STL model and the robot deposition path points, combining with the robot posture representation method of roll-pitch-yaw angles, the posture information of path points is achieved. Then, the generation from CAD model of parts to robot paths for laser melting is realized, and the experimental verification is carried out. Findings: For simple parts, the laser melting process can be completed without the posture information of deposition paths. However, in the melting process of a turbine blade, there are some accumulated burls on the sidewall. The posture generation method of robot deposition paths based on the intersection topology can solve this problem. The light spot of deposition points irradiates on the surface of the forming part, and the forming process can proceed smoothly. Practical implications: As a motion platform in laser melting deposition (LMD), the application of the multi-joint robot can improve the flexibility and deposition capability of the deposition system, as well as promote the LMD application for individuation manufacturing, parts repair and green remanufacturing. Originality/value: The posture is essential for robot deposition paths. This paper first proposes a posture generation method of deposition paths for LMD to improve the flexibility and deposition capability of LMD systems.